2022
DOI: 10.3389/fonc.2022.1029951
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic efficacy and prognostic factors of TACE plus TKI with ICIs for the treatment of unresectable hepatocellular carcinoma: A retrospective study

Abstract: Hepatocellular carcinoma (HCC) remains a global challenge due to its high morbidity and mortality rates as well as poor response to treatment. Local combined systemic therapy is widely used in the treatment of unresectable hepatocellular cancer (uHCC). This retrospective study was to investigate the prognostic effect and prognostic factors of transcatheter arterial chemoembolization (TACE) plus tyrosine kinase inhibitors (TKI) with immune checkpoint inhibitors (ICIs) in the treatment of uHCC. A retrospective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The reported mOS was 19.8 to 24.1 months for TTP and was 15.9 to not reached for HTP. [20][21][22][23] Consistent with our study, TACE-and HAIC-based combination therapies brought favorable and satisfying survival benefits in the treatment of advanced HCC, though significant differences in tumor response and survival outcomes between the two groups were not reached. However, the differences should not be ignored for they might be caused by the limited number of cases.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The reported mOS was 19.8 to 24.1 months for TTP and was 15.9 to not reached for HTP. [20][21][22][23] Consistent with our study, TACE-and HAIC-based combination therapies brought favorable and satisfying survival benefits in the treatment of advanced HCC, though significant differences in tumor response and survival outcomes between the two groups were not reached. However, the differences should not be ignored for they might be caused by the limited number of cases.…”
Section: Discussionsupporting
confidence: 85%
“…Han et al reported that TACE plus TKI and PD-1 inhibitors showed a mOS of 24.1 months, a mPFS of 10.6 months, ORRs of 42% and DCRs of 80%. 21 In addition, Guo et al demonstrated that the sequential combination of TACE with PD-1 inhibitors and TKIs for patients with advanced HCC significantly improved markers of treatment efficacy (mOS, 19.8 months; mPFS, 11.7 months; ORRs, 48.4%). 22 The combination therapies of HAIC, TKIs and PD-1 inhibitors have also been reported to have improved response rates and survival outcomes for unresectable HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…This study is the first international multicenter phase III clinical study of anti-PD-1 monoclonal antibodies in combination with an anti-vascular targeted small molecule tyrosine kinase inhibitor on PFS and OS outcomes over sorafenib, and camrelizumab in combination with apatinib treatment achieved the longest OS benefit to date. In patients with HCC with a large tumor burden that cannot be resected, advanced hepatic artery chemoembolization combined with AC has better survival than early combination ( 55 , 56 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Furthermore, the ORR and DCR of triple therapy patients in Huang et al presented better outcomes than ICIs + TKI groups (12.5% and 50.0%), 32 42% and 80% in a study by Han et al presented better outcome thanTACE groups (31.1% and 51.1%) and TACE+TKI groups (35.5% and 65.8%), respectively. 33 These studies show that triple therapy has an advantage in terms of efficacy. Our results are comparable to those of other single-center investigative studies.…”
Section: Discussionmentioning
confidence: 97%